Novel Systemic Inflammation Markers to Predict COVID-19 Prognosis - Karimi, Amirali; Shobeiri, Parnian; Kulasinghe, Arutha; Rezaei, Nima (Frontiers in Immunology, 2021)
COVID-19 has resulted in a global pandemic, challenging both the medical and scientific community for the development of novel vaccines and a greater understanding of the effects of the SARS-CoV-2 virus. COVID-19 has been associated with a pronounced and out-of-control inflammatory response. Several studies have sought to understand the effects of inflammatory response markers to prognosticate the disease. Herein, we aimed to review the evidence of 11 groups of systemic inflammatory markers for risk-stratifying patients and prognosticating outcomes related to COVID-19. Numerous studies have demonstrated the effectiveness of neutrophil to lymphocyte ratio (NLR) in prognosticating several outcomes, including but not limited to severe disease, hospitalization, intensive care unit (ICU) admission, intubation, and death. A few markers outperformed NLR in predicting some outcomes, including 1) systemic immune-inflammation index (SII), 2) prognostic nutritional index (PNI), 3) C-reactive protein (CRP) to albumin ratio (CAR) and high-sensitivity CAR (hsCAR), and 4) CRP to pre-albumin ratio (CPAR) and high-sensitivity CPAR (hsCPAR). However, there is a limited number of studies comparing NLR with these markers, and such conclusions require larger validation studies. Overall, the bulk of evidence suggests that most of the studied markers are able to predict COVID-19 prognosis, but NLR seemed to be the most studied and reliable one with proven prognosticating ability. We suggest researchers explore potentially useful but less studied markers and examine their cost-effectiveness.